GROWTH ATTRIBUTES AND RHIZOME YIELD OF SWEET FLAG (ACORUS CALAMUS L.) AS INFLUENCED BY SPACING - SINGH , M.SUMARJIT; NONGMAITHEM, (The Bioscan, 2013)
Acorus calamus (Sweet flag) is one of the endangered medicinal plants mostly grown in wild form without much attention. Hence, a study was undertaken for two consecutive years in the kharif season of 2010 and 2011 to assess the possibility of optimizing rhizome yield of sweet flag (A. calamus L.) by maintaining different spacing under field conditions. From the results of the experiment significant increase in rhizome length and weight was observed under wider spaced plants while significantly higher rhizome yield of A. calamus were recorded when planted with closer spacing of 20 cm × 30 cm (8624.52 kg ha-1) than those planted under wider spacing of 40 cm × 40 cm (6395.66 kg ha-1). Hence this study illustrates the different results obtained and the possibility of optimizing rhizome yield of A. calamus by maintaining proper plant spacing.